TINJAUAN YURIDIS TANTANGAN CROWDFUNDING DALAM RANGKA UPAYA PREVENTIF PENCEGAHAN KEJAHATAN EKONOMI - Ni Putu Yuliana Kemalasari; I Wayan Gede Subawa (Faculty of Law, Mahasaraswati University, Denpasar, 2024)
Peer to Peer Lending (P2PL) has emerged as a phenomenon in the financial landscape of Indonesia, providing easier access to funding for small and medium-sized enterprises (SMEs). However, this service also brings risks such as financial crimes and data privacy violations. In this context, it is crucial to examine the contractual agreements in P2PL, particularly concerning fairness and legal security for both parties involved. This article proposes an analysis of standard contracts in P2PL, tracing their legal framework and discussing their implications for fairness, utility, and legal certainty. Furthermore, the article highlights the risks of financial crimes in P2PL, including the roles of illegal operators and data privacy breaches. Considering the role of the Financial Services Authority (OJK) in regulating technology-based financial services, this research offers insights into the challenges and opportunities in maintaining the integrity and security of P2PL services in Indonesia.